Regulation of Oxygenic Photosynthesis during Trophic Transitions in the Green Alga Chromochloris zofingiensis. Issue 3 (20th February 2019) - Roth, Melissa S.; Gallaher, Sean D.; Westcott, Daniel J.; Iwai, Masakazu; Louie, Katherine B.; Mueller, Maria; Walter, Andreas; Foflonker, Fatima; Bowen, Benjamin P.; Ataii, Nassim N.; Song, Junha; Chen, Jian-Hua; et al.
Abstract : The unicellular green alga Chromochloris zofingiensis reversibly shuts down photosynthesis and reprograms its metabolism in response to the availability of glucose as a carbon source. Abstract: Light and nutrients are critical regulators of photosynthesis and metabolism in plants and algae. Many algae have the metabolic flexibility to grow photoautotrophically, heterotrophically, or mixotrophically. Here, we describe reversible Glc-dependent repression/activation of oxygenic photosynthesis in the unicellular green alga Chromochloris zofingiensis. We observed rapid and reversible changes in photosynthesis, in the photosynthetic apparatus, in thylakoid ultrastructure, and in energy stores including lipids and starch. Following Glc addition in the light, C. zofingiensis shuts off photosynthesis within days and accumulates large amounts of commercially relevant bioproducts, including triacylglycerols and the high-value nutraceutical ketocarotenoid astaxanthin, while increasing culture biomass. RNA sequencing reveals reversible changes in the transcriptome that form the basis of this metabolic regulation. Functional enrichment analyses show that Glc represses photosynthetic pathways while ketocarotenoid biosynthesis and heterotrophic carbon metabolism are upregulated. Because sugars play fundamental regulatory roles in gene expression, physiology, metabolism, and growth in both plants and animals, we have developed a simple algal model system to investigate conserved eukaryotic sugar responses as well as mechanisms of thylakoid breakdown and biogenesis in chloroplasts. Understanding regulation of photosynthesis and metabolism in algae could enable bioengineering to reroute metabolism toward beneficial bioproducts for energy, food, pharmaceuticals, and human health.